ANALYSIS OF THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON DIVIDEND POLICY IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - T. Hafifah Poetry Zulmi; Rico Nur Ilham; Muttaqien; Ristati (Universitas Efarina, 2023)
This research aims to determine the impact of good corporate governance as measured using the size of the board of commissioners, independent commissioners, size of the board of directors and leverage as control variables on dividend policy in property and real estate sector companies listed on the Indonesian stock exchange. This research uses a combination of cross section and time series data. The population from this research is 73 companies and the sample in this research is 28 companies using a purposive sampling technique. Data analysis used in this research uses the Panel Data Regression method with the help of the Eviews 10 application. The data used is secondary data which can be accessed via the official website www.idx.co.id. The research results found that the size of the board of commissioners had a positive and insignificant effect on dividend policy, independent commissioners had a positive and insignificant effect on dividend policy, the size of the board of directors had a positive and insignificant effect on dividend policy.